2019
DOI: 10.3389/fmicb.2019.00385
|View full text |Cite
|
Sign up to set email alerts
|

The Phytoplankton Taxon-Dependent Oil Response and Its Microbiome: Correlation but Not Causation

Abstract: Phytoplankton strongly interact with their associated bacteria, both attached (PA), and free-living (FL), and bacterial community structures can be specific to phytoplankton species. Similarly, responses to environmental stressors can vary by taxon, as exemplified by observed shifts in phytoplankton community structure from diatoms to phytoflagellates after the Deepwater Horizon (DWH) oil spill. Here, we assess the extent to which associated bacteria influence the phytoplankton taxon-specific oil response by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…This study also showed that algal‐attached communities in seawater are different from bulk particle‐associated communities, indicating that phycosphere communities are specific and distinct from the regional species pool. The Rhodobacteraceae and Flavobacteriaceae reported here are common members of dinoflagellate microbiomes, whereas Planctomycetes are rare or absent in dinoflagellate microbiome sequence sets (Hasegawa et al ., ; Severin and Erdner, ; Sörenson et al ., ). Crenn and colleagues () compared microbiomes of diatoms from cultures and environmental samples, and reported lower diversity in the former.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that algal‐attached communities in seawater are different from bulk particle‐associated communities, indicating that phycosphere communities are specific and distinct from the regional species pool. The Rhodobacteraceae and Flavobacteriaceae reported here are common members of dinoflagellate microbiomes, whereas Planctomycetes are rare or absent in dinoflagellate microbiome sequence sets (Hasegawa et al ., ; Severin and Erdner, ; Sörenson et al ., ). Crenn and colleagues () compared microbiomes of diatoms from cultures and environmental samples, and reported lower diversity in the former.…”
Section: Discussionmentioning
confidence: 99%
“…2b) and strains growing on crude oil (Table 3) were observed in the bacterial community associated to Nitzschia. This suggests that these associated hydrocarbonoclastic bacteria may enhance biodegradation of PAHs in non-axenic cultures, as previously highlighted (Mishamandani et al, 2016;Thompson et al, 2017Thompson et al, , 2018Severin and Erdner, 2019). The degradation of PAHs by microorganisms depends on their molecular weight, hydrophobicity, and water solubility (Haritash and Kaushik, 2009).…”
Section: Pah Accumulation and Biodegradationmentioning
confidence: 54%
“…The presence of oil-and hydrocarbon-degrading bacteria within the phycosphere has been reported for dinoflagellates and diatoms (Gutierrez et al, 2012;Mishamandani et al, 2016;Severin et al, 2016;Thompson et al, 2017Thompson et al, , 2018. These associated bacteria can influence the phytoplankton taxon-specific response to hydrocarbon pollution and oil spills (Severin and Erdner, 2019). Most studies have concerned planktonic microalgae and their associated bacteria, but little is known about the PAH biodegradation potential of microbenthic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above changes in microbial community activity, it was also found that the mucus-like EPS harbored a very distinct community of interacting microbes, with a specific functionality that was different from those persisting in the surrounding seawater (Ziervogel et al, 2012;Arnosti et al, 2015). These eukaryotic microbes and fungi can transform and degrade oil, sometimes in association with bacteria and dispersants including Corexit (Mishamandani et al, 2016;Severin and Erdner, 2019). Thus, marine snow is a hot spot for microbial activity (Azam, 1998;Arnosti et al, 2015;Doyle et al, 2018Doyle et al, , 2020 and serves as a transport vehicle for hydrocarbons to the seafloor as well as the associated microbial communities (Kowalewska and Konat, 1997;Kowalewska, 1999;Ziervogel et al, 2012;Ziervogel et al, 2014Ziervogel et al, , 2016Arnosti et al, 2015).…”
Section: How Do Microbes Respond To Oil and Dispersants?mentioning
confidence: 99%